Settlement of Inherited Land Disputes Due to Transfer of Rights on the Basis of Sale and Purchase - Marliah, Yeyen; Dwi Istinah, Siti Rodhiyah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze: 1) Legal protection for heirs in disputes over the sale and purchase of inherited land sold by adopted children without the consent of the heirs intestasto. 2). The judge's considerations in determining the decision to settle inherited land disputes as a result of the transfer of rights on the basis of sale and purchase in decision number: 01/Pdt.G/2013/PN.TGL. The approach method used in this research is a normative juridical approach. The specification of the research used is descriptive analytical research. Type of data using secondary data. The data analysis method used in this research is descriptive qualitative analysis. The results of the study concluded: 1) Legal protection for heirs in disputes over the sale and purchase of inherited land sold by adopted children without the approval of intestasto heirs, namely that can be realized through complaints to the National Land Agency (BPN) and by filing lawsuits in court. If it is proven that there is an element of forgery and an element against the law, the judge will cancel the sale and purchase. The cancellation of the deed of sale and purchase is a form of repressive protection given to the heirs of inherited land that is sold without the consent of the heirs intestasto. 2) The judge's considerations in determining the decision to settle an inherited land dispute as a result of the transfer of rights on the basis of sale and purchase in the decision number: 01/Pdt.G/2013/PN.TGL, namely the basis for the judge's consideration has fulfilled justice for the land owner because the intestasto heirs have property rights of the land and the heirs may not be harmed. The deed of sale and purchase of the object of the dispute is proven to have violated a person's subjective rights as well as decency, as stipulated in Article 1365 of the Civil Code, and therefore the Defendants here have committed an unlawful act.Keywords: Buy; Dispute; Inheritance.